Crowdsourcing for the Identification and Conservation of the Floral Diversity of Nepal: A Technological Perspective - Sharma, Gajendra; Adhikari, Subarna (Yayasan Ahmar Cendekia Indonesia, 2019)
Nepal is rich in biodiversity in terms of both flora and fauna. While significant effort has been given to the conservation of wild animals, rare or otherwise, same cannot be said for the floral diversity of the country. In fact, due to significant challenges, the floral diversity of the country remains largely unexplored. The system proposed in this paper tries to overcome those challenges by using technology to aid the collection of information about the floral diversity of the country by crowdsourcing at a local level, using the image data collected for the plant identification by using machine learning or through expert users/volunteers.